EXPRESSION OF SPIRITUAL AND MORAL PROBLEMS IN THE DRAMA - Kholmatova Nigora Yakubovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the folk writer of Uzbekistan E. Azam's drama "The Maid's Dream" and the new artistic interpretation of the important, spiritual, moral, and social problems inherent in this drama are analyzed.